Computer-assisted virtual preoperative planning in orthopedic surgery for acetabular fractures based on actual computed tomography data. Issue 1 (1st January 2016) - Wang, Guang-Ye; Huang, Wen-Jun; Song, Qi; Qin, Yun-Tian; Liang, Jin-Feng
Abstract: Acetabular fractures have always been very challenging for orthopedic surgeons; therefore, appropriate preoperative evaluation and planning are particularly important. This study aimed to explore the application methods and clinical value of preoperative computer simulation (PCS) in treating pelvic and acetabular fractures. Spiral computed tomography (CT) was performed on 13 patients with pelvic and acetabular fractures, and Digital Imaging and Communications in Medicine (DICOM) data were then input into Mimics software to reconstruct three-dimensional (3D) models of actual pelvic and acetabular fractures for preoperative simulative reduction and fixation, and to simulate each surgical procedure. The times needed for virtual surgical modeling and reduction and fixation were also recorded. The average fracture-modeling time was 45 min (30–70 min), and the average time for bone reduction and fixation was 28 min (16–45 min). Among the surgical approaches planned for these 13 patients, 12 were finally adopted; 12 cases used the simulated surgical fixation, and only 1 case used a partial planned fixation method. PCS can provide accurate surgical plans and data support for actual surgeries.